THE EFFECTIVENESS OF USING GUIDED DISCOVERY IN TEACHING READING COMPREHENSION - Ida Zahara (Edukasi, 2017)
The objectives of this study were to find out whether or not there was any significant difference in reading comprehension achievement between the students who were taught by using guided discovery and those who were taught by using conventional strategy to the eleventh grade students of MAN Arahan. This research was conducted through quasi-experimental method and used matching only pre-test post-test control group design. The population was 140 students of the eleventh grade of MAN Arahan in the academic year 2012/2013. Seventy students were chosen as the sample by using convenience sampling technique. The sample were assigned into two groups; the experimental group and the control group. Each group consisted of thirty five students. The data were obtained by reading comprehension test. A test was given both to the experimental group and control group before and after the treatment. The result of the test was analyzed by using matched t-test. The result of the study showed that there was any significant difference between eleventh grade students of MAN Arahan who were taught by using guided discovery and those who were taught by conventional strategy. The t-obtained was 4.52 at the significant level 0.05 in two tailed testing and df=21, the critical value of t-table is 2.080. Since the value of t-obtained was higher than t-table, then the null hypothesis was rejected and the alternative hypothesis was accepted. It can be stated that guided discovery is effective in teaching reading comprehension, and can be used as the alternative technique for teaching reading comprehension to the eleventh grade students of MAN Arahan.